2014
DOI: 10.1007/s12011-014-0172-8
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Physical Activity on Hair Toxic and Essential Trace Element Content in Male and Female Students

Abstract: The primary aim of the current study is to estimate the effect of different physical activity levels on hair trace element content in male and female students. A total of 113 students (59 women and 54 men) of P. G. Demidov Yaroslavl State University (Yaroslavl, Russia) took part in the current investigation. According to the level of the physical activity, all students were divided into three groups: high, medium, and low physical activity. Essential and toxic metal content (μg/g) in hair samples was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 31 publications
3
9
1
1
Order By: Relevance
“…At the same time, a recent study failed to reveal gender differences in hair Se content in healthy population and persons with non-alcoholic steatohepatitis (Pan and Huang 2013). Our research data conform to the results of our previous study indicating higher hair V levels in male students in comparison to females (Zaitseva et al 2015). The observed gender difference in Cr values is caused by higher intake of the metal in men (Anderson and Kozlovsky 1985).…”
Section: Resultssupporting
confidence: 89%
“…At the same time, a recent study failed to reveal gender differences in hair Se content in healthy population and persons with non-alcoholic steatohepatitis (Pan and Huang 2013). Our research data conform to the results of our previous study indicating higher hair V levels in male students in comparison to females (Zaitseva et al 2015). The observed gender difference in Cr values is caused by higher intake of the metal in men (Anderson and Kozlovsky 1985).…”
Section: Resultssupporting
confidence: 89%
“…These results are in line with previously described ones that students, involved in high physical activities, have an increased Se level [14].…”
Section: Resultssupporting
confidence: 93%
“…However, in our study Fe demonstrated decreased concentration in hair samples, which can be related to both geographical differences and to the age of studies groups (Table 2) [14].…”
Section: Resultscontrasting
confidence: 48%
“…The detection limit of Se with ICP-MS was 0.01 μg/g. Rapid, quasi-simultaneous, multielement detection capabilities, high sensitivity, and detection power have made this technique an important tool for the analysis of trace elements in biological samples [42][43][44]. All of the reagents were of analytical-reagent grade or better, provided by Sino-pharm Chemical Reagent, Beijing, China.…”
Section: Sample Digestion and Analysismentioning
confidence: 99%